The Applicability of Constitutional Court Decision Number 118/PUU-XX/2022 Regarding the Statute of Limitations for Document Forgery in Relation to the New Criminal Code - Hizkia, John Michael (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Constitutional Court Decision Number 118/PUU-XX/2022 altered the policy for calculating the statute of limitations for the crime of document forgery; however, the implementation of the new Criminal Code does not reflect this change. This study employs a normative approach, using a literature review to analyze the applicability of the Constitutional Court’s decision to the new Criminal Code, which does not incorporate this change. The findings of the study indicate that, based on the principle of lex posterior derogat legi priori, the current regulations still adhere to Constitutional Court Decision 118/2022, as the new Criminal Code will not take effect until 2026. Should a material review related to this article arise in the future, the Constitutional Court must apply the principle of similia similibus to ensure justice and prevent discrimination, thereby guaranteeing equal treatment for all individuals under the law